Female caregivers accompanying children with cancer in the hospital setting. - Wegner, Wiliam; Pedro, Eva Neri Rubim (Revista Gaúcha de Enfermagem, 2011)
The possibility of having a companion is a constitutional right guaranteed to children, elderly and parturients. Independently of their stage in the life cycle, having a companion is a situation socially and culturally determined in Brazil. This is a qualitative, descriptive-exploratory and interventionist study that aims to describe and discuss the perceptions of female caregivers of children with cancer while accompanying them at the hospital. Data were collected through a focal group with nine women, between March and May, 2007 at a teaching hospital in Porto Alegre, Rio Grande do Sul, Brazil. The thematic analyses shows the participants’ passive and kind behavior in the face of daily adversities, reflection of the power and authority conditions of the institutional objectives, so common in health scenarios in the Brazilian reality. Emancipation could be reached through educative strategies, characterized by information and dissemination of users’ rights as well as critical and demanding attitudes from the user when confronted.